Peran Komitmen dan Motivasi Kerja dalam mempengaruhi Kinerja Karyawan - Aula Rakhmawati; Nadia Alfrida Hermayani; Woro Utari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to examine and analyze the effect of employee commitment and work motivation on employee performance. The unit of analysis in this study were all employees at the Griya Elderly Santo Yosef Foundation on which operates 60 people. Sampling using saturated sampling technique. Data analysis was performed using statistics with SPSS tool. Based on the results of data analysis using the t test, it is know that partially employee commitment and work motivation have a significant effect on work commitment. Based on the results of data analysis using the F test, it is known that simultaneously employee commitment and work motivation have a significant effect on employee performance.